Characterization of chitosan and carboxymethyl chitosan films from various sources and molecular sizes - P. Rachtanapun (2018)
Carboxymethyl chitosan (CMCH) from different sources (shrimp, crab and squid) and molecular sizes (polymer and oligomer) was synthesized via carboxymethylation with monochloroacetic acid (MCA) in isopropyl alcohol (IPA) under alkaline condition. Next, chitosan and CMCH films were prepared and their properties were studied. Crystallinity, mechanical properties [tensile strength (TS) and percent elongation at break (EB)], water vapor transmission rate (WVTR), and color change were investigated. The crystallinity and TS value of each CMCH film was less than that of chitosan. The highest TS (28.6 MPa) was provided by chitosan film from crab oligomer (CO). The CMCH films from various types displayed the higher EB value comparing with those of chitosan films. The CMCH film from shrimp polymer (SP) exhibited the highest EB value (44%). The WVTR of each CMCH films were interestingly lower than that of chitosan, and the lowest value was obtained by the CMCH film from crab oligomer (CO) (15 g/m 2×day 1). The CMCH films showed higher color L * and a * value but lower b * value comparing with those of chitosan films from the same type. © (2012) Trans Tech Publications.